FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN DI INDONESIA - Khakim, Luqmanul; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Timeliness of financial reporting is an important characteristic for financial statements where the reported financial reports in a timely manner will reduce asymmetric information. When companies postpone financial reporting to the public then information can not be used for decision making. The longer time delayed in presenting the financial statements of a company to the public, the more likely there is insider information about the company. This study aims to determine the factors that affect the timeliness of financial reporting. The research was conducted at automotive company listed in Bursa Efek Indonesia, with year of research from 2011 until 2015. The analysis technique used in this research is multiple linear regression analysis, with F test and t test. Based on the results of this study can be seen that profitability has a positive and significant impact on timeliness, firm size has a positive and significant impact on timeliness, and the age of the company has a negative and insignificant effect on timeliness.Keywords: profitability, audit opinion, firm size, company age, timelinessÂ